Design and Implementation of High Performance UWB Horn Antenna - Nan Hu; Wenqing Xie; Jianrui Liu; Shuang Liu; Lixin Zhao; Changyong Yuan, (Applied Computational Electromagnetics Society Journal (ACES), 2019)
Broadband horn antennas have been widely used in radar and communication systems. They have also been added to various state-of-the-art control systems to perform EMC measurements. EMC measurements traditionally use standard gain horn antennas for many practical reasons like needing 8 standard antennas to test a wide range of frequencies (e.g., 0.75-18 GHz). This results in space efficiency reductions (e.g., the anechoic chambers efficiency is reduced). To solve this problem, an ultra-wideband (UWB) double-ridged horn antenna is designed and tested in this study. The antenna exhibits improved gains, VSWRs, and radiation patterns. Radiation patterns maintain a single main lobe across the full band. This signifies that the designed antenna can fulfill the desired higher demands. We have fabricated the antenna and it has been applied to many related fields.